The LncRNA CASC11 Promotes Colorectal Cancer Cell Proliferation and Migration by Adsorbing miR-646 and miR-381-3p to Upregulate Their Target RAB11FIP2 - Zhang, Wei; Li, Xiaomin; Zhang, Wenjuan; Lu, Yanxia; Lin, Weihao; Yang, Lawei; Zhang, Zheying; Li, Xuenong (Frontiers in Oncology, 2021)
Background: We previously reported that the long non-coding RNA (lncRNA) CASC11 promotes colorectal cancer (CRC) progression as an oncogene by binding to HNRNPK. However, it remains unknown whether CASC11 can act as a competitive endogenous RNA (ceRNA) in CRC. In this study, we focused on the role of CASC11 as a ceRNA in CRC by regulating miR-646 and miR-381-3p targeting of RAB11FIP2. Methods: We identified the target microRNAs (miRNAs) of CASC11 and the target genes of miR-646 and miR-381-3p using bioinformatic methods. A dual-luciferase reporter assay was performed to validate the target relationship. Quantitative real-time PCR (qRT-PCR), western blotting (WB), and immunohistochemistry (IHC) were used to measure the RNA and protein expression levels. Rescue experiments in vitro and in vivo were performed to investigate the influence of the CASC11/miR-646 and miR-381-3p/RAB11FIP2 axis on CRC progression. Results: We found that CASC11 binds to miR-646 and miR-381-3p in the cytoplasm of CRC cells. Moreover, miR-646 and miR-381-3p inhibitors reversed the suppressive effect of CASC11 silencing on CRC growth and metastasis in vitro and in vivo. We further confirmed that RAB11FIP2 is a mutual target of miR-646 and miR-381-3p. The expression levels of CASC11 and RAB11FIP2 in CRC were positively correlated and reciprocally regulated. Further study showed that CASC11 played an important role in regulating PI3K/AKT pathway by miR-646 and miR-381-3p/RAB11FIP2 axis. Conclusion: Our study showed that CASC11 promotes the progression of CRC as a ceRNA by sponging miR-646 and miR-381-3p. Thus, CASC11 is a potential biomarker and a therapeutic target of CRC.